Where Are Antipsychotics Prescribed in Nursing Homes Initiated? - Zhang, Yan (J Am Geriatr Soc, 2018)
OBJECTIVE: To describe the settings of care in which antipsychotics that nursing home (NH) residents received were likely to have been initiated. DESIGN: Cross-Sectional. SETTING: Iowa NHs. PARTICIPANTS: Fee-for-service Medicare beneficiaries who had NH stays between January 1, 2011, and December 31, 2014, and had new use of antipsychotics during their NH stays, defined as no antipsychotic use in NHs in the last 6 months. MEASUREMENTS: A linked dataset of Chronic Condition Data Warehouse Medicare Claims and Long Term Care Minimum Data Set 3.0 (MDS 3.0) was used to determine care settings of antipsychotic initiations. RESULTS: Of 7,496 residents with new antipsychotic use in NHs, 4,794 (64.0%, 95% confidence interval (CI) = 62.9–65.0%) initiated them in NHs, 1,392 (18.6%, 95% CI = 17.7–19.5%) appeared to have had them initiated in hospitals, and 1,310 (17.5%, 95% CI = 16.6–18.3%) had antipsychotics first dispensed as outpatients. Antipsychotics were commonly prescribed during the early NH stays, and 3,026 (40.4%, 95% CI = 39.3–41.5%) of the entire sample received antipsychotic therapy within the first 7 days after NH admissions. Fifty-eight percent (n = 4,348) of the study residents initiating antipsychotics had potentially appropriate antipsychotic indications according to MDS records. CONCLUSIONS: Most residents initiated antipsychotic therapy in NHs, confirming that NH providers are appropriate primary target of interventions to reduce antipsychotic initiation in their residents. However, many antipsychotics were continued from other settings, indicating a need to evaluate the necessity of continued antipsychotic treatment after such transitions of care.